Pasar Modal Syariah Dalam Perspektif Tafsīr Ahkām Maudhu’i - Andika, Musa (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2022)
Islamic classical literature does not use capital market terminology that is in accordance with Islamic law. As a Muslim, one must ensure that investments made in the capital market are in accordance with Islamic law, according to the verse. Regarding the issues raised in this article, in particular: First, what are the arguments relating to the Islamic capital market? Second, how is Akhkam Maudhu'i's interpretation of the effects of the Islamic capital market? The writing of this article uses the analytical method used, namely normative legal analysis. Primary law and secondary materials should be used for retrieval of necessary legal materials. The conclusion of this paper the authors conclude that Islamic capital market transactions can be carried out by: A contract of buying and selling securities, does not contain elements of usury, there is no falsehood, seeking God's bounty, trustworthy goals, mutual pleasure. The Islamic capital market is in the form of buying and selling halal shares and is justified in Islamic teachings, both the Qur’an and the Hadith of the Prophet.